Towards Convergence in Europe: Institutions, Labour and Industrial Relations - Daniel Vaughan-Whitehead (Edward Elgar Publishing, 2019)
This book aims to answer a number of important questions. To what extent have European countries converged or diverged with EU-wide economic and social indicators over the past 20 years? What have been the drivers of convergence? Why do some countries lag behind, while others experience continuous upward convergence? Why are these trajectories not always linear? Particular attention is paid to the role of institutions, actors and industrial relations - focusing on the resources and strategies of governments, employers and trade unions - in nudging EU countries onto an upward convergence path.